Conditioned Media from Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Inhibits Melanogenesis by Promoting Proteasomal Degradation of MITF. - Eun Sung Kim; Hong Bae Jeon; Hoon Lim; Ji Hyun Shin; So Jung Park; Yoon Kyung Jo; Wonil Oh; Yoon Sun Yang; Dong-Hyung Cho; Ju-Yeon Kim (PLoS ONE, 2015)
Human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) secrete various beneficial molecules, which have anti-apoptotic activity and cell proliferation. However, the effect of hUCB-MSCs in melanogenesis is largely unclear. In this study, we show that conditioned media (CM) derived from hUCB-MSCs inhibit melanogenesis by regulating microphthalmia-associated transcription factor (MITF) expression via the ERK signalling pathway. Treatment of hUCB-MSC-CM strongly inhibited the alpha-melanocyte stimulating hormone-induced hyperpigmentation in melanoma cells as well as melanocytes. Treatment of hUCB-MSC-CM induced ERK1/2 activation in melanocytes. In addition, inhibition of ERK1/2 suppressed the anti-pigmentation activity of the hUCB-MSC-CM in melanocytes and in vitro artificial skin models. We also found that the expression of MITF was appreciably diminished while expression of phosphorylated MITF, which leads to its proteasomal degradation, was increased in cells treated with hUCB-MSC-CM. These results suggested that hUCB-MSC-CM significantly suppresses melanin synthesis via MITF degradation by the ERK pathway activation.